Effect of Amniotic Membrane-Derived Mesenchymal Stem Cells on TNF-? Expression and Inflammatory Cells Infiltration during Vesicovaginal Fistule Repair Healing Process - Eighty Mardiyan Kurniawati1, Agung Nur Rachman W1, Budi Santoso1, Harry Parathon1, Widjiati2, Fedik (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Vesicovaginal fistula (VVF) causes high morbidity in women, affecting both physical and psychological condition. Until now, surgery is the mainstay treatment for this condition. However, prolonged exposure during inflammatory phase after surgery is still a problem in the healing process. TNF-? as potent pro-inflammatory cytokine plays an important role by attracting inflammatory cells to wound tissue. Amniotic membrane is the source for mesenchymal stem cells that had anti-inflammatory and imunomodulatory effect. This study aims to evaluate the effect of Amniotic Membrane-Derived Mesenchymal Stem Cells (AMMSC) on TNF-? expression and inflammatory cell infiltration during VVF repair healing process in New Zealand White (NZW) rabbit model. Method: This study was an experimental study with randomized posttest only control group design. Twentyseven NZW rabbit as VVF model was used in this study, randomly divided into 3 different treatment groups after underwent surgical treatment (no treatment <C group>, treated with freeze-dried amniotic membrane <T1 group>, and treated with freeze-dried amniotic membrane that seeded with AMMSC <T2 group>). Evaluation was done 7 days after treatment. TNF-? expression was evaluated semiquantitatively using modified Remmele-Stegner scale. Inflammatory cell infiltration was evaluated using modified Klopfleisch method. Results: Mean TNF-? expression between C, T1, and T2 group were significantly different (8.5 ± 1.6; 7.1 ± 1.2; 1.6 ± 1.2 respectively, p < 0.001). Median inflammatory cell infiltration between C, T1, and T2 group were significantly different (3.0; 2.0; 1.0 respectively, p < 0.001). Conclusion: AMMSC significantly reduced TNF-? expression and inflammatory cells infiltration during VVF repair healing process.